Antimicrobial agents production by fungi isolates from the whisperers - AL-Jarrad, Rafal Sattar Jabbar; Shadahan , Ali Mohaisn (Scientific Journal of Medical Research, 2025)
Objective: The current study aimed to screen of local fungi isolates for antimicrobial bioactive compounds production. Methods: Fifteen samples of whisperer’s soil were analyzed for antimicrobial producing by fungi. Seven species of fungi were obtained from these samples, these fungi were Aspergillus niger, Aspergillus ochraceus, Aspergillus flavus, Penicillium notatum, Bacillomyces sp., Trichoderma sp. and Cladosporium sp. and the filtrate of each fungal isolate given special label as AA, AB, AC, AD, AE, AF and AG, respectively. These fungal filtrates were tested their antimicrobial activity against three Gram positive bacteria (Staphylococcus sp., Streptococcus agalicae and Bacillus sp.) also three Gram negative bacteria (Enterobacter sp., Pseudomonas sp. and Klebsiella sp.) by disc technique. Results: Bacillus sp. was the most sensitive to all fungal filtrations, especially for AC (Aspergillus flavus) and AE (Bacillomyces sp.) where the inhibition zone were the largest compared to the antibiotic which used, the inhibition zones were (6 and 5.33) mm, respectively. Streptococcus agalicae was affected only by AD (Penicillinum notatum) and AG (Cladosporium sp.) with inhibition zone (4 and 3.33) mm, respectively. In Gram negative bacteria, Enterobacter sp. is highly sensitive to AG (Cladosporium sp.) with inhibition zone 7 mm. Conclusion: Some species of fungi which have antibacterial activity can be isolated from the soil of whisperers.